L-SCRaMbLE as a tool for light-controlled Cre-mediated recombination in yeast - Lena Hochrein (Nature Portfolio, 2018)
The International Synthetic Yeast Sc2.0 project has built Cre recombinase sites into synthetic chromosomes, enabling rapid genome evolution. Here the authors demonstrate L-SCRaMbLE, a light-controlled recombinase tool with improved control over recombination events.